Epilepsy Care in the Time of COVID-19 Pandemic in Italy: Risk Factors for Seizure Worsening - Assenza, Giovanni; Lanzone, Jacopo; Brigo, Francesco; Coppola, Antonietta; Di Gennaro, Giancarlo; Di Lazzaro, Vincenzo; Ricci, Lorenzo; Romigi, Andrea; Tombini, Mario; Mecarelli, Oriano (Frontiers in Neurology, 2020)
Objective In early 2020 Italy struggled with an unprecedent health emergency related to COVID-19 pandemic. Medical care of chronic neurologic diseases, such as epilepsy, are being forcefully neglected. In this national survey we aimed at understanding the impact of COVID-19 breakdown on people with epilepsy (PwE) care and identifying PwE risk factors for seizure worsening to direct telemedicine efforts. Methods We administered a 48-items online survey (published on April 11, 2020) including socio-demographic, epilepsy-related and psychometric variables (BDI-II for depression, GAD-7 for anxiety, PSQI for sleep) to PwE and persons without epilepsy (PwoE). Regression analysis identified predictors of seizure worsening. Results We collected 879 responses from 427 PwE (327 females, 38.6±11.8 years) and 452 PwoE (331 females, 43.89±12.25 years). Outpatient examinations of PwE were postponed in 95% of cases. One third of PwE complained issues with epilepsy management, but only 71% of them reached the treating physician and solved their problems. PwE had worse BDI-II and GAD-7 (p<0.001) scores than PwoE. Sleep quality was equally compromised in both groups (47% and 42%). Sixty-seven PwE (18%) reported seizure worsening. Worsening in PwE was best explained by the number of anti-seizure medications (ASM) and the severity of sleep disorder. Conclusions: During current COVID-19 pandemic, a significant percentage of PwE experienced difficulties in follow-up and seizure worsening, in particular those with more ASMs and bad sleep quality. This dramatic experience outlines the urgent need for validation and implementation of telemedicine services for epileptic patients in order to provide regular follow-up.